Three-Dimensional Quantification of Cam Resection Using MRI Bone Models: A Comparison of 2 Techniques. Issue 5 (6th May 2022) - Alter, Thomas D.; Knapik, Derrick M.; Guidetti, Martina; Espinoza, Alejandro; Chahla, Jorge; Nho, Shane J.; Malloy, Philip
Background: The current clinical standard for the evaluation of cam deformity in femoroacetabular impingement syndrome is based on radiographic measurements, which limit the ability to quantify the complex 3-dimensional (3D) morphology of the proximal femur. Purpose: To compare magnetic resonance imaging (MRI)–based metrics for the quantification of cam resection as derived using a best-fit sphere alpha angle (BFS-AA) method and using 3D preoperative-postoperative surface model subtraction (PP-SMS). Study Design: Descriptive laboratory study. Methods: Seven cadaveric hemipelvises underwent 1.5-T MRI before and after arthroscopic femoral osteochondroplasty, and 3D bone models of the proximal femur were reconstructed from the MRI scans. The alpha angles were measured radially along clockfaces using a BFS-AA method from the literature and plotted as continuous curves for the pre- and postoperative models. The difference between the areas under the curve for the pre- and postoperative models was then introduced in the current study as the BFS-AA–based metric to quantify the cam resection. The cam resection was also quantified using a 3D PP-SMS method, previously described in the literature using the metrics of surface area (FSA), volume (FV), and height (maximum [FHmax ] and mean [FHmean ]). Bivariate correlation analyses were performed to compare the metrics quantifying the cam resection as derived from the BFS-AA and PP-SMS methods. Results: The mean ± standard deviation maximum pre- and postoperative alpha angle measurements were 59.73° ± 15.38° and 48.02° ± 13.14°, respectively. The mean for each metric quantifying the cam resection with the PP-SMS method was as follows: FSA, 540.9 ± 150.7 mm 2 ; FV, 1019.2 ± 486.2 mm 3 ; FHmax, 3.6 ± 1.0 mm; and FHmean, 1.8 ± 0.5 mm. Bivariate correlations between the BFS-AA–based and PP-SMS–based metrics were strong: FSA ( r = 0.817, P = .012), FV ( r = 0.888, P = .004), FHmax ( r = 0.786, P = .018), and FHmean ( r = 0.679, P = .047). Conclusion: Strong positive correlations were appreciated between the BFS-AA and PP-SMS methods quantifying the cam resection. Clinical Relevance: The utility of the BFS-AA technique is primarily during preoperative planning. The utility of the PP-SMS technique is in the postoperative setting when evaluating the adequacy of resection or in patients with persistent hip pain with suspected residual impingement. In combination, the techniques allow surgeons to develop a planned resection while providing a means to evaluate the depth of resection postoperatively.